EDUCATING IN INEQUALITY: PSYCHOPEDAGOGY, VULNERABILITY AND ETHICAL RESISTANCE IN CONTEMPORARY BRAZIL - Mathylde Soares, Ângela; de Aquino Noffs, Neide (Revista Gênero e Interdisciplinaridade, 2025)
This study investigates the relationship between socioeconomic vulnerability and access to basic education in Brazil, with a particular emphasis on the regional provision of psychopedagogical services. Grounded in the assumption that education is inherently non-neutral, the article positions psychopedagogy as a central clinical-educational field responsible for listening, intervening, and reimagining life trajectories. The findings reveal glaring regional disparities, indicating the urgent need for revised public policies, context-sensitive investments, and targeted affirmative actions. “In every region of Brazil, a unique way of learning pulses. But to truly hear these ways, more than methods are required: we need poetry, presence, and ethics.”